2005
DOI: 10.1370/afm.312
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension and Cardiovascular Morbidity

Abstract: PURPOSEThe Seventh Report of the Joint National Commission (JNC 7) on High Blood Pressure established prehypertension (120 to 139 mm Hg systolic or 80 to 89 mm Hg diastolic) as a new risk category. We aim to determine the risk of major cardiovascular events associated with blood pressure in the prehypertensive range in a longitudinal, population-based cohort.METHODS Analyses were conducted on participants in the National Health and Nutrition Examination Survey I (1971Survey I ( -1975 observed for 18 years for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
135
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(147 citation statements)
references
References 25 publications
(21 reference statements)
7
135
1
4
Order By: Relevance
“…13,[27][28][29][30][31][32][33] Likewise, a number of large-scale cohort studies have reported significant effects of prehypertension separately on the risks of stroke 13,29,30,32 and coronary heart disease. 13,29 The present analysis from the APCSC confirmed the results from the previous observational studies and provided more detailed information about the separately significant associations of prehypertension with all of the major types of CVD, including ischemic and hemorrhagic stroke in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…13,[27][28][29][30][31][32][33] Likewise, a number of large-scale cohort studies have reported significant effects of prehypertension separately on the risks of stroke 13,29,30,32 and coronary heart disease. 13,29 The present analysis from the APCSC confirmed the results from the previous observational studies and provided more detailed information about the separately significant associations of prehypertension with all of the major types of CVD, including ischemic and hemorrhagic stroke in the Asia-Pacific region.…”
Section: Discussionmentioning
confidence: 99%
“…However, Seventh Report of the Joint National Committee (JNC-7) provides a newer guideline on classification of hypertension [5,6]; SBP between 120-139 mmHg or DBP between 80-89 mmHg fall into prehypertension [7] and possess higher cardiovascular and renal risk in future [8,9]. Prehypertension is commonly prevalent in the general population [10] but there are only a few studies on the prevalence and risk factors available in Indians [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…6 This is increasingly being shown to be an independent risk factor of hypertension 7,8 and cardiovascular morbidity. [9][10][11] In addition, individuals with prehypertension are a potential target population for promotion of lifestyle modifications aimed at prevention of hypertension and cardiovascular diseases. Little is known about the magnitude of prehypertension and its associated factors in Africa.…”
Section: Introductionmentioning
confidence: 99%